N-acetylcysteine supplementation of HIV-infected patients under the first anti-retroviral treatment: Evaluation of the effect on viral load, TNF-α, IL-6, IL-8, β2-microglobulin, IgA, IgG, IgM, haptoglobin and α1-acid glycoprotein (Revista Brasileira de Ciências Farmacêuticas, 2002)
Human immunodeficiency virus infection is associated with a progressive elevation of viral load and with a continuous destruction of the immune cellular defense system which is marked by immunological and inflammatory disorders characteristic of HIV-infected individuals. These alterations are characterized by elevated levels of tumor necrosis factor alpha (TNF-α), interleukin 8 (IL-8), β2-microglobulin, IgA, IgG, IgM, haptoglobin and a1-acid glycoprotein. The goal of this double blind placebo-controlled study was to evaluate the effect of N-acetylcysteine supplementation on virological, immunological and inflammatory markers in 24 HIVinfected individuals who were taking their first anti-retroviral therapy. Eleven individuals were treated with anti-retroviral therapy plus placebo supplementation and thirteen were treated with anti-retroviral therapy plus 600 mg/day of Nacetylcysteine. The levels of the studied markers were evaluated at the day before and after 60, 120 and 180 days of treatment. In both groups a significant decrease in serum levels of TNF-α (p=0.0001), IL-6 (p>;0.05), IL-8 (p=0.0001), b2 microglobulin (p=0.0005), IgA (p=0.007), IgG (p=0.001), IgM (p=0.0001), haptoglobin (p=0.0001) e α1-acid glycoprotein (p=0.012) was found due to anti-retroviral therapy. N-acetylcysteine supplementation had no additive or synergistic effects on the studied parameters. In conclusion, N-acetylcysteine had no additional beneficial effects, at least at the dose used in this study, on the treatment of HIV-infected patients under anti-retroviral therapy.